STUDY ON THE CAUSES OF CRACKS & SPALLED MATERIAL IN HIGH PRESSURE DIE CASTING DIES FOR CRANK CASE PART AT AUTOMOTIVE COMPANY - Mentari Wahyuningtyas, Lina
High pressure die casting process is an effective process used in automotive industry because of its high production rate and good surface quality. Nonetheless it also has weakness which the dies are often damaged, whilst dies are the most important component in the casting process. Premature failure that happened to high pressure die casting (HPDC) dies tremendously intrudes the manufacturing process. Automotive company X is dealing with early cracks problem on AISI H13 (mod) steel made dies for crank case part that appeared before the dies achieved product’s target count. The limitation of the company is to perform detail and profound failure analysis. The aims of this research are to determine the causes of cracks and spalled material, also to understand the failure mechanisms so that corrective acts and/or improvement plan making can be carried out. Observation and several characterization methods were done to acquire datas used for considerations in the analysis process. Characterizations that were conducted are chemical compositions using OES, Vickers hardness test, metallography, SEM, and EDS. Based on the results obtained from tests, one data and the others indicate that the specimens experienced thermal fatigue with attributes shown; brittle fracture surface, intergranular cracks, and the presence of beach marks on the fracture surface. Moreover, spalling phenomenon was also encountered by the material, these voids formed cracks and reached out to the surface. Both phenomenons was initiated by sub-surface voids and surface pitting which produced by nitriding process.